Community-based programs - National Association of Social Workers (Social Work Abstracts)
Dans Social Work abstracts, le terme Social innovation est présent mais peu utilisé. Le terme "community-based programs" permet de trouver plus de documents.
http://opurl.bib.umontreal.ca:8331/V/P5M7MTANMHTJP8UAIV4LK7A9VYVM3VF2L86YU8KX9UGTUJUKCJ-02468?func=native-link&resource=MON06004
Keywords: Thésaurus de base de données; Travail social

Community-based programs - National Association of Social Workers (Social Work Abstracts)
Dans Social Work abstracts, le terme Social innovation est présent mais peu utilisé. Le terme "community-based programs" permet de trouver plus de documents.
http://opurl.bib.umontreal.ca:8331/V/P5M7MTANMHTJP8UAIV4LK7A9VYVM3VF2L86YU8KX9UGTUJUKCJ-02468?func=native-link&resource=MON06004
Keywords: Thésaurus de base de données; Travail social

Social Innovation - McMillin, Stephen Edward (Encyclopedia of Social Work, 2021)
Social innovation is not well understood within the context of macro-social work. Frameworks for understanding social innovation as having dimensions of social entrepreneurship, social intrapreneurship, and social advocacy are elaborated. Challenges to the comprehensive understanding and utility of social innovation for macro social work are discussed, especially an overemphasis on social entrepreneurship as the only typical expression of social innovation as well as a mistargeted, deficit-based approach which assumes that contemporary social work is dysfunctional and can only be made functional through social innovation and entrepreneurship. Global and multidisciplinary insights and applications of social innovation for macro social work are reviewed. Finally, how the macro-social work approach to social innovation builds on and advances business approaches to social innovation is discussed.
ISBN: 9780199975839 Rassemble plusieurs définitions de l’innovation sociale
Keywords: Entrepreneuriat social; Ouvrages de référence; Réservé UdeM; Travail social

Social Innovation - McMillin, Stephen Edward (Encyclopedia of Social Work, 2021)
Social innovation is not well understood within the context of macro-social work. Frameworks for understanding social innovation as having dimensions of social entrepreneurship, social intrapreneurship, and social advocacy are elaborated. Challenges to the comprehensive understanding and utility of social innovation for macro social work are discussed, especially an overemphasis on social entrepreneurship as the only typical expression of social innovation as well as a mistargeted, deficit-based approach which assumes that contemporary social work is dysfunctional and can only be made functional through social innovation and entrepreneurship. Global and multidisciplinary insights and applications of social innovation for macro social work are reviewed. Finally, how the macro-social work approach to social innovation builds on and advances business approaches to social innovation is discussed.
ISBN: 9780199975839
Keywords: Ouvrages de référence; Réservé UdeM; Travail social